Omega-3 Fatty Acid Supplements for Chronic Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
Omega-3 fatty acid (FA) supplements (lg EPA and 0.7g DHA daily) were used in the treatment of 58 patients with refractory epilepsy, in a 12-week double-blind, placebo-controlled trial conducted by researchers at the UCL Institute of Neurology, London, UK.